Design And Control Modelling of An IoT-Enabled Solar-Powered Ac Lighting System with Embedded Power Conversion - Amar, Ishak; Wawan Mariki, I Wayan; Fahri Anwar; Achmad Romadin (Journal of Renewable Energy and Smart Device, 2026)
This study investigates the performance of a photovoltaic-based power conversion and wireless monitoring system designed for small-scale renewable energy applications. The proposed system integrates a DC–AC inverter, closed-loop voltage regulation, and wireless communication using an embedded controller to enable stable power delivery and real-time monitoring. Experimental testing was conducted under varying irradiance and load conditions to evaluate electrical performance, conversion efficiency, dynamic response, and communication behavior. The results show that output power increased proportionally with irradiance, reaching a maximum of 53.27 W at 1000 W/m². The inverter demonstrated stable conversion efficiency in the range of 86.40%–89.11%, with an average efficiency of 87.94%, indicating effective power conversion across different operating conditions. Dynamic response analysis revealed an overdamped behavior with no observable overshoot and voltage ripple below 5%, confirming stable voltage regulation and agreement with the proposed second-order transfer function model. In addition, the wireless monitoring subsystem operated reliably, with Wi-Fi providing lower response time than Bluetooth for real-time control and monitoring purposes. Overall, the experimental results confirm that the proposed system is capable of achieving stable electrical performance, efficient energy conversion, and reliable wireless communication, making it suitable for standalone solar lighting and other small-scale distributed renewable energy applications.